Espaços não formais de educação ambiental como ferramenta de sensibilização e conscientização socioambiental no município de Araraquara-SP (Revista Brasileira Multidisciplinar, 2022)
Non-formal education occurs in spaces where there are intentional interactive processes that are collectively constructed. The non-formal spaces of environmental education (EE) are places where people can experience how the natural environment is essential for the maintenance of ecosystem relationships that guarantee the maintenance of life in all its forms. In this sense, the aim of this article is to present an experience report of an EE program, developed for students from the 6th to the 9th year of elementary school at a public school in the city of Araraquara. For the 6th grade students, an eco-pedagogical trail was programmed from the school to the spring of the Água Branca stream, and for the 7th, 8th and 9th grade students, monitored technical visits were programmed to the Fonte Luminosa Water Treatment Station, Araraquara Sewage Plant and Solid Waste Treatment Station/Acácia Recyclable Material Collectors Cooperative. The selection of these places was made in order to allow students to get to know, throughout the final years of elementary school, the entire chain of environmental sanitation of Araraquara. The monitored visits, in addition to contributing to the understanding of the technical aspects related to the sanitation chain, are configured as an important tool for reflection on the relationships established between human beings and nature and between human beings themselves, reinforcing the socio-environmental bias of EE. Works in this direction can contribute to the construction of more robust and effective EE programs, towards a transformative education.
Keywords: monitored visits; environmental educator spaces; environmental education; VerdeAzul Municipality Program